(untitled) (Itinera, 2025)
Perception and biodiversity. Phenomenological reflections for a relational model Over the past few decades, the concept of biodiversity, since its initial formulation in 1986, has become central to both the academic and public debate as a means of evaluating the human impact on the well-being of the natural environments. In the face of challenges posed by climate change, this concept emphasizes the consequences of human actions and promotes a better management practice of the problem. This paper proposes a critical reflection on the philosophical premises underlying the concept of biodiversity, highlighting its limitations and advancing an alternative proposal. Rather than adopting an evaluation criterion focused on individuals, it suggests considering processes and relationships among living beings, adopting an aesthetic perspective, understood as the study of perception and interaction with the world. Through an analysis of Merleau-Ponty’s phenomenology, a new theoretical model is proposed, one that conceives biodiversity as a system of relationships, thus redefining the identity of living beings as well. This relational approach offers a more dynamic vision of biodiversity, with significant implications for understanding and managing contemporary environmental crises.